1999
DOI: 10.1287/mnsc.45.12.1613
|View full text |Cite
|
Sign up to set email alerts
|

Bundling Information Goods: Pricing, Profits, and Efficiency

Abstract: W e study the strategy of bundling a large number of information goods, such as those increasingly available on the Internet, and selling them for a fixed price. We analyze the optimal bundling strategies for a multiproduct monopolist, and we find that bundling very large numbers of unrelated information goods can be surprisingly profitable. The reason is that the law of large numbers makes it much easier to predict consumers' valuations for a bundle of goods than their valuations for the individual goods when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
318
1
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(335 citation statements)
references
References 17 publications
7
318
1
9
Order By: Relevance
“…The client has a more stable expectation of the value of a collection of information on a particular topic. Bakos and Brynjolfson (1999) demonstrate that bundling is profitable for publishers, but the same arguments apply to an information intermediary developing a menu of information offerings from a variety of information producers. It becomes easier to assess the average consumer's valuation and price services appropriately when there are a large number of goods.…”
Section: Intermediaries and Information Distributionmentioning
confidence: 82%
“…The client has a more stable expectation of the value of a collection of information on a particular topic. Bakos and Brynjolfson (1999) demonstrate that bundling is profitable for publishers, but the same arguments apply to an information intermediary developing a menu of information offerings from a variety of information producers. It becomes easier to assess the average consumer's valuation and price services appropriately when there are a large number of goods.…”
Section: Intermediaries and Information Distributionmentioning
confidence: 82%
“…The latter question is of particular interest since the monopoly pricing literature has shown that the gains from bundling large numbers of products can be substantial (Armstrong, 1999;Bakos and Brynjolfsson, 1999). The rank order of issues becomes very informative as the number of issues increases so the communication gains from bundling are also likely to be significant.…”
Section: Resultsmentioning
confidence: 99%
“…The rank order of issues becomes very informative as the number of issues increases so the communication gains from bundling are also likely to be significant. 3 Bundling does not always increase payoffs. For large u it is rare that both issues are desired enough to make a bundle worthwhile so no bundling is preferred.…”
Section: Resultsmentioning
confidence: 99%
“…2 An important distinction between the two groups of models is that in the latter group, each product is competing with all others, while in the former consumers are truly heterogeneous in their preferences, and some products may have no overlap, i.e., may never be in direct competition. 3 In this paper we adopt the locational approach, which in our view better captures consumer heterogeneity and allows the explicit consideration of participation constraints that inevitably arise when dealing with a spatial distribution of endowed unobservable consumer characteristics. Our model is inspired by Salop's "circular city" [30], which we extend to a "cylinder" by adding a vertical product characteristic.…”
Section: Literature Reviewmentioning
confidence: 99%